2013
DOI: 10.1371/journal.pone.0079668
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Both the Cultivable Protease-Producing Bacteria and Bacterial Extracellular Proteases in the Coastal Sediments of King George Island, Antarctica

Abstract: Protease-producing bacteria play a vital role in degrading sedimentary organic nitrogen. However, the diversity of these bacteria and their extracellular proteases in most regions remain unknown. In this paper, the diversity of the cultivable protease-producing bacteria and of bacterial extracellular proteases in the sediments of Maxwell Bay, King George Island, Antarctica was investigated. The cultivable protease-producing bacteria reached 105 cells/g in all 8 sediment samples. The cultivated protease-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 23 publications
(28 reference statements)
4
35
0
2
Order By: Relevance
“…Particulate organic nitrogen (PON) that deposits to marine sediments is mainly decomposed by bacterial extracellular proteases, which is generally considered to be the initial and rate-limiting step of nitrogen cycle in marine sediments (Talbot and Bianchi, 1997; Brunnegård et al, 2004). It has been found that protease-producing bacteria and their extracellular proteases are rich and diverse in marine sediments (Olivera et al, 2007; Zhou et al, 2009, 2013). Some proteases from marine sedimentary bacteria have been characterized, most of which are shown to have special properties, such as cold adaptation (Chen et al, 2007; Yan et al, 2009; Kurata et al, 2010; Yang et al, 2013), salt tolerance (Yan et al, 2009), distinct substrate specificity and catalytic mechanism (Ran et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate organic nitrogen (PON) that deposits to marine sediments is mainly decomposed by bacterial extracellular proteases, which is generally considered to be the initial and rate-limiting step of nitrogen cycle in marine sediments (Talbot and Bianchi, 1997; Brunnegård et al, 2004). It has been found that protease-producing bacteria and their extracellular proteases are rich and diverse in marine sediments (Olivera et al, 2007; Zhou et al, 2009, 2013). Some proteases from marine sedimentary bacteria have been characterized, most of which are shown to have special properties, such as cold adaptation (Chen et al, 2007; Yan et al, 2009; Kurata et al, 2010; Yang et al, 2013), salt tolerance (Yan et al, 2009), distinct substrate specificity and catalytic mechanism (Ran et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In two other reports, Pseudoalteromonas from the sediments of South China Sea and Bacillus spp. from the coastal sediments of King George Island produced extracellular proteases (Zhou et al 2009a, b;Zhou et al 2013). In our study, we identified diverse protease-producing isolates from HV1 and HV2, most of which belonging to the Bacillus genus.…”
Section: Isolates That Exhibited Two Types Of Extracellular Activitymentioning
confidence: 60%
“…The genus Lacinutrix which belongs to the phylum Bacteroidetes currently consists of five type species and members of the genus Lacinutrix have been known to produce extracellular protease in marine sediments of Antarctica (Bowman and Nichols, 2005;Nedashkovskaya et al, 2008;Srinivas et al, 2013;Zhou et al, 2013;Lee et al, 2014). Type strains of the genus Lacinutrix were all isolated from copepod, algae, or sediments of polar areas (Bowman and Nichols, 2005;Nedashkovskaya et al, 2008;Srinivas et al, 2013;Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%